The Impact of Principal’s Leadership Style on Teachers’ Work Ethic and Professional Competence - Herlinda Purnama; Nur Hayati (Jurnal Pendidikan Progresif, 2024)
The Influence Of The Principal's Leadership Style On The Work Ethic And Professional Competence Of Teachers. Objectives: This study investigates the influence of the principal’s leadership style on the work ethic and professional competence of teachers in selected schools. The research focuses on three leadership styles: transformational, transactional, and democratic, analyzing their respective impacts on teacher performance. Methods: A quantitative approach was employed, using a survey method to collect data from 100 teachers at Kabupaten Sleman Yogyakarta. Correlation and regression analyses were conducted to examine the relationships between leadership styles and the two dependent variables: teacher work ethic and professional competence. Findings: The findings reveal that transformational leadership has the strongest positive effect on both work ethic and professional competence, with significant correlations and high regression values. Democratic leadership also showed a positive influence, promoting collaboration and teacher empowerment. However, transactional leadership had a comparatively weaker impact, focusing primarily on short-term compliance rather than fostering long-term growth. Conclusion: These results suggest that school principals should adopt transformational and democratic leadership styles to enhance teacher performance and create a motivating and supportive work environment. This research contributes to the broader understanding of educational leadership and its role in shaping teacher behavior, offering practical recommendations for improving school leadership practices. Keywords: principal leadership style, transformational leadership, transactional leadership.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024140